2019
DOI: 10.1016/j.fm.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of iturin A from B. amyloliquefaciens BUZ-14 in the inhibition of the most common postharvest fruit rots

Abstract: The aim of this work was to elucidate the role of the secondary metabolites produced by B. amyloliquefaciens BUZ-14 against B. cinerea, M. fructicola, M. laxa, P. digitatum, P. italicum and P. expansum both in vitro and in planta. The entire cell free supernatant (CFS) and the lipopeptide fraction (LPF) showed similar antifungal activities, completely inhibiting all the fungi at dilutions of 1:24 or even lower, whereas the nonbutanolic fraction (NBF) barely inhibited the fungi. However, when the LPF and CFS we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Previous studies have reported that the treatment of plant tissues (fruits, leaves) with cell suspensions, cell cultures, and cell free culture supernatant from BCAs gave very low values (<1–2 μg/g plant tissue) [ 14 , 54 , 55 ], raising questions about how to achieve the accumulation of active metabolites near or over the threshold levels required for antibiosis and/or induction of host plant defense mechanisms [ 54 ]. Recent studies have shown that bacterial colonization may generate microcolonies on the target tissue, where secondary metabolites are accumulated in micromolar amounts in microniches [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that the treatment of plant tissues (fruits, leaves) with cell suspensions, cell cultures, and cell free culture supernatant from BCAs gave very low values (<1–2 μg/g plant tissue) [ 14 , 54 , 55 ], raising questions about how to achieve the accumulation of active metabolites near or over the threshold levels required for antibiosis and/or induction of host plant defense mechanisms [ 54 ]. Recent studies have shown that bacterial colonization may generate microcolonies on the target tissue, where secondary metabolites are accumulated in micromolar amounts in microniches [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thin layer chromatography (TLC) analysis of ESC1 and ESC2 and bioautography was conducted as described previously [ 54 ]. TLC was performed using silica gel 60 F254 plates (20 × 20 cm; layer thickness, 0.20 mm; Merck) and chloroform–methanol–water (65:25:4, v / v / v ) as mobile phase.…”
Section: Methodsmentioning
confidence: 99%
“…Bacillomycin L is presumed to act by inducing membrane permeabilization and disruption, as well as by targeting intercellular structrues [91]. Iturins have been found to be effective against a number of plant pathogenic fungi, which include Botrytis , Penicillium, Monilinia [92], R. solani [93], Colletotricum [94], F. oxysporum [95,96,97], and F. graminearum [19,26].…”
Section: Overview Of Bacillus Species As a Protective Agent Againsmentioning
confidence: 99%
“…[23][24][25][26] Iturin exhibit the antifungal activity against a number of fungal phytopathogens including F. graminearum, F. oxysporum, R. solani, Penicillium, Monilinia, Botrytis and Colletotricum. 26,[27][28][29] Surfactin: Surfactin are lipopeptides composed of β-hydoxyhepta cyclic depsipeptides with potential combinations of alanine, valine, leucine or isoleucine amino acids at positions 2, 4 and 7 in the cyclic depsipeptide moiety and variations of C13 to C16 in the chains of β-hydroxy fatty acids. 30 Surfactin exhibits naturally antifungal activity and produce by Bacillus spp.…”
Section: Biocontrol Agents Of Bacillus Speciesmentioning
confidence: 99%